2017
DOI: 10.14283/jpad.2017.45
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Guarana (Paullinia Cupana Mart.) Against Vincristine in Vitro Exposure

Abstract: Background: Vincristine (VCR) is not a specific chemotherapeutic drug, responsible for cause several side effects. In this sense, many natural products have been studied to reduce this problem. Objetives: To examine the guarana neuroprotective effect in mice brain and cerebellum cells against vincristine (VCR) exposition. Design: An in vitro study was performed using mice brain and cerebellum mice in monolayer culture. First, cells were exposed to VCR (0.009 µM for 24 hours and 0.0007 µM for 72 hours) to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Evidence has shown that guaraná presents strong antioxidant and radical‐ scavenging properties (Maldaner et al, 2020 ; Roggia et al, 2020 ; Santana & Macedo, 2018 ; Yonekura et al, 2016 ), protective cellular and anti‐inflammatory properties (Machado et al, 2021 ), neuroprotective effect (Veloso et al, 2018 ), and anti‐aging proprieties (Arantes et al, 2018 ) An epidemiological study reported guaraná habitual consumption by older adult riverine with a lower prevalence of hypertension, obesity, and metabolic syndrome (da Costa Krewer et al, 2011 ). Yonekura et al ( 2016 ) had shown that small daily doses of guaraná (3 g) can improve oxidative stress markers in healthy subjects (Yonekura et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence has shown that guaraná presents strong antioxidant and radical‐ scavenging properties (Maldaner et al, 2020 ; Roggia et al, 2020 ; Santana & Macedo, 2018 ; Yonekura et al, 2016 ), protective cellular and anti‐inflammatory properties (Machado et al, 2021 ), neuroprotective effect (Veloso et al, 2018 ), and anti‐aging proprieties (Arantes et al, 2018 ) An epidemiological study reported guaraná habitual consumption by older adult riverine with a lower prevalence of hypertension, obesity, and metabolic syndrome (da Costa Krewer et al, 2011 ). Yonekura et al ( 2016 ) had shown that small daily doses of guaraná (3 g) can improve oxidative stress markers in healthy subjects (Yonekura et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, vincristine increases ROS production and causes a cellular imbalance in different brain regions in rats, via lipoperoxidation (Martins et al, 2011), indicating a close relationship between vincristine and oxidative stress, since ROS is a major contributor to neurodegeneration. In a study, using cerebral and cerebellar cells from mice exposed to vincristine (0.009 μM for 24 h and 0.0007 μM for 72 h), the hydroalcoholic extract of guarana (10, 30, 100 and 300 μg/mL) increased cell viability by stimulating CAT activity (10, 30 and 100 μg/mL), as well as reducing ROS and lipoperoxidation levels (Veloso et al, 2017) (Figure 3).…”
Section: Effects Of Paullinia Cupana Kunth -Neuroprotective Potential...mentioning
confidence: 99%
“…The neuroprotective effect of guarana in mouse cerebellar cells and brain neurons against vincristine exposure was investigated in an in vitro study. P. cupana increased cell viability, stimulated catalase activity, and reduced lipoperoxidation and ROS levels [ 171 ]. The effects of P. cupana consumption on erythrocyte antioxidant enzyme activity, plasma catechins, and oxidative stress biomarkers in healthy, overweight subjects were evaluated.…”
Section: Specific Nootropic Herb Shrub and Tree Speciesmentioning
confidence: 99%